Analysis of Obstacles in Evaluating Student Learning through School Collaboration (SMAN 1 Medan, SMAN 2 Medan, and SMAN 3 Medan) - Derita Ramai Durubanua; Nurmala Berutu; Fatimah Azzahra; Regita Asiah Azzarah; T. Abdillah Azis (Universitas Muhammadiyah Enrekang, 2024)
This research aims to analyze obstacles in evaluating student learning through collaboration between schools at SMAN 1 Medan, SMAN 2 Medan, and SMAN 3 Medan, and provide solutions to overcome these obstacles. The method used is qualitative research with a case study approach. Data collection was carried out through interviews, observation and document analysis involving 3 teachers selected using purposive sampling. The research results show that the main obstacle faced by teachers is a lack of in-depth understanding of the concept of Technological Pedagogical Content Knowledge (TPACK) and difficulties in selecting appropriate technology. Many teachers feel less confident and less skilled in integrating technology into learning evaluation, which has an impact on low evaluation quality and student engagement. Solutions identified to overcome these obstacles include training and professional development focused on TPACK as well as collaborating with educational technology experts. Implementing this solution requires support and commitment from the school and government. This research recommends increasing teachers' understanding and skills in TPACK to improve the quality of learning evaluation and proposes an inter-school collaboration model as an effective strategy for overcoming similar obstacles.